Characterization of Valley-Fill Alluvial Aquifers in Plutonic and Volcanic Semi-arid Andes Using Electromagnetic Methods: The Case of the Limarí Catchment (Chile) - de Pasquale, Giulia; Bresciani, Etienne; Valois, Rémi; Álvarez Latorre, Pablo A. (Frontiers in Water, 2022)
areas of the world are facing sustained periods of water resource stress during which the enhanced exploitation of groundwater is key to maintaining irrigation and drinking water supplies. A good knowledge about groundwater resources is therefore essential to develop sustainable water management strategies. In this study, we aimed to characterize a mountainous watershed in the semi-arid Chilean Andes. The area of interest is distinguished by a high topographic gradient and narrow valleys filled with sedimentary deposits of various origins and surrounded by plutonic and volcano-sedimentary rocks. To characterize the hydrostratigraphy of this complex sedimentary system and to estimate the volume of groundwater stored, we implemented a multidisciplinary approach integrating geophysical data from transient electromagnetic sounding (TEM), hydrogeological, geological, geomorphological and groundwater quality information. The results indicate the presence of two aquifer layers in the majority of the investigated area: a superficial unconfined aquifer and a deeper confined (or semi confined) aquifer. We found that the width and depth of the sedimentary deposits increase with decreasing topography, while the proportion of fine material increases, in coherence with the sedimentation processes. Finally, we quantified the groundwater contribution of the different areas of the catchment and identified the main aquifer potential area in the pediplanes of the coastal mountain range (storing approximately 67% of the water available for extraction). The main contributions to the total uncertainties on the groundwater storage (ranging between 30 and 80% of the estimated volumes) are due to the propagation of the uncertainty on the thickness and porosity/specific yield of the modeled hydrostratigraphic layers. Due to the large spacing between TEM soundings and the limited number of stratigraphic bore logs in part of the studied area, the obtained characterization should be integrated with additional data for precise borehole sittings. Nevertheless, the implementation of TEM allowed to cover an extensive area and to reach large depth of exploration, so that it was possible to extract general information about the hydrostratigraphy of the different areas of the catchment.